Postbiotic gel relieves clinical symptoms of bacterial vaginitis by regulating the vaginal microbiota - Shen, Xin; Xu, Lin; Zhang, Zhiquan; Yang, Yitong; Li, Pengxian; Ma, Teng; Guo, Shuai; Kwok, Lai-Yu; Sun, Zhihong (Frontiers in Cellular and Infection Microbiology, 2023)
Vaginitis is the most common disease in gynecology. Vaginal dysbiosis is a main reason of bacteria vaginitis (BV), as the disrupted microecological environment facilitates the growth of various vaginal pathogens. The most dominant bacteria in the vaginal microbiota are lactic acid bacteria, which are important for maintaining vaginal health. At present, antibiotics and other drugs are often used in clinical treatment, but there are many adverse reactions and easy to relapse, and the intervention of probiotics can help restore vaginal microbiota and alleviate BV. This study is a human clinical trial of 50 patients with bacterial vaginitis (BV). The alleviation effect of applying a postbiotic gel for one week in BV was evaluated. Changes in patients’ clinical indicators of BV (properties of vaginal secretion) and the vaginal microbiota after using the postbiotic gel were monitored. Our results showed that apply the postbiotic gel improved the symptoms of BV, indicated by improvement in the abnormalities of patients’ vaginal secretions. After applying the gel, the relative abundance of vaginal lactobacilli increased compared to baseline. Significant negative correlations were found between lactobacilli and potential vaginal pathogens (including Gardnerella, Prevotella, and Atopobium), as well as the abnormalities of the vaginal secretion. Overall, our results showed that applying the postbiotic gel ameliorated BV, and the symptom improvement was accompanied by significant changes in the bacterial vaginal microbiota. Our study provides valuable clinical data in managing BV.